2017
DOI: 10.1093/nsr/nwx142
|View full text |Cite
|
Sign up to set email alerts
|

Global leaf nitrogen and phosphorus stoichiometry and their scaling exponent

Abstract: Leaf nitrogen (N) and phosphorus (P) concentrations constrain photosynthetic and metabolic processes, growth and the productivity of plants. Their stoichiometry and scaling relationships regulate the allocation of N and P from subcellular to organism, and even ecosystem levels, and are crucial to the modelling of plant growth and nutrient cycles in terrestrial ecosystems. Prior work has revealed a general biogeographic pattern of leaf N and P stoichiometric relationships and shown that leaf N scales roughly as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
113
6
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 142 publications
(160 citation statements)
references
References 54 publications
25
113
6
2
Order By: Relevance
“…4), which was consistent with the results of Fyllas et al (2009) and other studies about plant nutrient stoichiometry at global scales (Han et al, 2011;Zhao et al, 2016;Tian et al, 2017). Further, the interactive effects of climatic factors with life forms were higher than the independent explanations of climate (0.7-15.7 %, Fig.…”
Section: Discussionsupporting
confidence: 91%
“…4), which was consistent with the results of Fyllas et al (2009) and other studies about plant nutrient stoichiometry at global scales (Han et al, 2011;Zhao et al, 2016;Tian et al, 2017). Further, the interactive effects of climatic factors with life forms were higher than the independent explanations of climate (0.7-15.7 %, Fig.…”
Section: Discussionsupporting
confidence: 91%
“…This study also provides important implications for the parameterization in modelling stoichiometric growth and nutrient cycles in terrestrial ecosystems (Niklas et al, ; Peñuelas et al, ; Tang et al, ; Wright et al, ), and for understanding plant adaptation and evolution under varying nutrient environments (Kerkhoff et al, ). Moreover, our results consolidate one recent finding that there is no universal N‐P scaling exponent (Tian et al, ). The general 0.667‐power law of leaf N versus P scaling (Reich et al, ) may be counterintuitive when considering the role of nutrient changes.…”
Section: Discussionsupporting
confidence: 91%
“…Based on a global dataset of leaf N and P concentrations with more than 9,300 pairwise entries, Reich et al () noted that variation in the scaling exponent from specific case studies likely arose from insufficient sample sizes, and concluded that the scaling exponent was a uniform constant of 0.667 across major life‐forms and biomes. In contrast, one recent study cautioned against the ubiquity of the general 0.667‐power law and revealed inconstant scaling exponents across multiple scales based on analyses of one more comprehensive global dataset of leaf N and P concentrations (Tian et al, ). Further, the effects of nutrient addition on the coupling of N and P in terrestrial ecosystems have been studied extensively (e.g., Bracken et al, ; Ostertag & DiManno, ; Deng, Hui, Dennis, & Reddy, ).…”
Section: Introductionmentioning
confidence: 99%
“…Element concentrations and mass ratios of epiphytes differed significantly among functional groups and organs (Figure ). Differences among functional groups are also widespread in other terrestrial plants (Güsewell, ; Han et al, ; Sardans et al, ; Tian et al, ). In this study, these differences might be caused by the large differences in morphological, anatomical, and physiological traits among lichens, bryophytes, ferns, and spermatophytes that led to differences in nutrient uptake, nutrient metabolism, and nutrient retention (Aerts & Chapin, ; Benzing, ).…”
Section: Discussionmentioning
confidence: 99%
“…The ecological stoichiometry in plants can be influenced not only by environmental factors but also by species, organs, and functional types. In large‐scale studies, the elemental composition and stoichiometry of terrestrial plants are influenced by forest type, climate, and soil (Chen, Han, Tang, Tang, & Fang, ; Han, Fang, Reich, Woodward, & Wang, ; Sardans et al, ; Tian et al, ). In a European forest, the identity of tree species can explain 56.7% of the variance of the overall foliar elemental composition and stoichiometry (Sardans et al, ).…”
Section: Introductionmentioning
confidence: 99%